Combined Determination of Glucose and Fructosamine in Vitreous Humor as a Post-Mortem Tool to Identify Antemortem Hyperglycemia (The Review of Diabetic Studies, 2023)
In clinical practice, serum glucose levels are used to diagnose diabetes mellitus. In post-mortem diagnosis, however, biochemical markers in vitreous humor are more useful because of the difficulty involved in interpreting blood glucose levels and relatively non-specific pathological features. The aim of this study was to analyze the usefulness of post-mortem determination of glucose and fructosamine combined and to compare the results with those obtained for fructosamine and combined glucose and lactate levels in two diagnostic groups (one diabetic and the other non-diabetic). We studied 377 cadavers (mean age 57.6 yr, SD 20.4, range 15 to 98 yr) with a mean post-mortem interval of 14.9 h. (SD 6.0; range 2 to 24 h). The highest levels were obtained in cases where diabetes mellitus had previously been diagnosed. In relation to diagnostic performance, the most reliable values were those in which glucose and fructosamine were determined jointly. The findings provide information concerning the usefulness of measuring glucose and fructosamine levels as a post-mortem tool for identifying antemortem glycemic control in diabetics.